(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
It is known that the mining and metallurgical industry in Uzbekistan is a leading sector of the economy. Therefore, special attention is paid to the expansion of production capacity and efficiency in this area, the widespread use of modern technological capabilities. The fact that the head of our state has paved the way for consistent reforms to ensure the future prospects of Uzbek industry lays the foundation for the development of the mining and metallurgical industry in our country, including the production of ferrous and non-ferrous metals